2014
DOI: 10.14233/ajchem.2014.15301
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Carbon Dioxide in Ethanolamine Solutions

Abstract: Ethanolamine solutions are a kind of important absorbent for carbon dioxide capture from flue gas. In this work, the absorption rate and absorption capacity of carbon dioxide by ethanolamine and piperazine solutions have been studied. Using a newly absorption equipment, the absorption rate was measured in monoethanolamine, diethanolamine and piperazine solutions with different concentration from 10 to 50 wt %, respectively. The experimental results showed that monoethanolamine and diethanolamine both have a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…This means that as the concentration of amino acids increases, the reaction rate between Alanine, Arginine, piperazine and CO 2 increases with concentration to the power of 1.22−2. The present trends are in accordance with the findings of [40][41][42].…”
Section: B Effect Of Absorbent Type (K 2 Co 3 Mea) On Co 2 Absorptionsupporting
confidence: 93%
“…This means that as the concentration of amino acids increases, the reaction rate between Alanine, Arginine, piperazine and CO 2 increases with concentration to the power of 1.22−2. The present trends are in accordance with the findings of [40][41][42].…”
Section: B Effect Of Absorbent Type (K 2 Co 3 Mea) On Co 2 Absorptionsupporting
confidence: 93%
“…A blend of MDEA and Pz has the potential to combine the high capacity of MDEA with the attractive kinetics of Pz (Peter, 2014). Piperazine is a common absorbent, which is used principally as an active agent to activate ethanolamine solutions (Lu, 2014). Besides, there is solubility limitation for Pz in water, that's why Pz is usually used as the promoter to mix with other alkanolamines for the enhancement of reaction rate with CO 2 (Tan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 desorption ratios and the pH values for the MEA solution without CaCl 2 added when it was treated at different temperatures (25,40,60, and 80 °C) with either ultrasound irradiation or stirring for 5 min are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all the commercial applications of MEA that have been reported have used high MEA concentrations, but the use of low MEA concentrations described in studies has not been widely published. [25][26][27] We previously performed a study in which we aimed to determine whether using ultrasound irradiation and a flow of N 2 gas could facilitate the desorption of CO 2 from an MEA solution at a low temperature. We found that less energy was required to desorb CO 2 from a solution with a low MEA concentration (0.2 mol=l) when the solution was kept at 25 °C and ultrasound irradiation was applied than when the solution was kept at 49 °C and stirred at 1,500 rpm.…”
Section: Introductionmentioning
confidence: 99%